The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1029/2006je002794
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the atmosphere of Venus below the clouds

Abstract: [1] The composition of Venus' lower atmosphere, beneath the clouds, has been investigated through both in situ measurements and remote-sensing observations. In 1978 the mass spectrometers and gas chromatographs aboard the Venera 11-12 landers and Pioneer Venus Large probe returned unique information on the abundances of carbon dioxide, nitrogen, noble gases, and other minor species. Radio occultations from the Pioneer and Magellan spacecraft provided measurements of the vertical profile of sulfuric acid vapor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…Subsequent observations [Marcq et al, 2005; found a global average cO mixing ratio of 24 ± 2 ppm at 36 km with a vertical gradient of 0.6 ± 0.3 ppm/km and a larger abundance of cO at 20-40° S latitude than at 0-20° S. Marcq et al [2005; also found a global average OcS mixing ratio of 0.55 ± 0.15 ppm at 36 km with a vertical gradient of -0.28 ± 0.1 ppm/km and a smaller abundance of OcS at 20-40° S latitude than at 0-20° S. The newer observations of cO are quantitatively consistent with the earlier results where the observational altitudes agree, although the best fit vertical gradient for cO is a factor of two smaller in the newer results. The smaller gradient in cO mixing ratio from Marcq et al [2005; is more consistent with measurements by instruments on Pioneer Venus and Venera 12 [Bezard and de Bergh, 2007] as shown in Plate 3. The best fit mixing ratio and the vertical gradient for OcS from the newer observations are a factor of eight and five, respectively, smaller than the earlier results.…”
Section: Ground-based Observations Of the Lower Atmospheresupporting
confidence: 73%
See 3 more Smart Citations
“…Subsequent observations [Marcq et al, 2005; found a global average cO mixing ratio of 24 ± 2 ppm at 36 km with a vertical gradient of 0.6 ± 0.3 ppm/km and a larger abundance of cO at 20-40° S latitude than at 0-20° S. Marcq et al [2005; also found a global average OcS mixing ratio of 0.55 ± 0.15 ppm at 36 km with a vertical gradient of -0.28 ± 0.1 ppm/km and a smaller abundance of OcS at 20-40° S latitude than at 0-20° S. The newer observations of cO are quantitatively consistent with the earlier results where the observational altitudes agree, although the best fit vertical gradient for cO is a factor of two smaller in the newer results. The smaller gradient in cO mixing ratio from Marcq et al [2005; is more consistent with measurements by instruments on Pioneer Venus and Venera 12 [Bezard and de Bergh, 2007] as shown in Plate 3. The best fit mixing ratio and the vertical gradient for OcS from the newer observations are a factor of eight and five, respectively, smaller than the earlier results.…”
Section: Ground-based Observations Of the Lower Atmospheresupporting
confidence: 73%
“…recently published measurements of their abundances are summarized in Table 1, Table 3, de Bergh et al [2006], and Bezard and de Bergh [2007]. h 2 S was reported by Pioneer Venus below 20 km [Hoffman et al, 1980], but it was never confirmed by an independent measurement and the reported value is at least an order of magnitude larger than would be expected from thermochemical equilibrium calculations [Fegley et al, 1997b].…”
Section: Sulfur Chemistrymentioning
confidence: 74%
See 2 more Smart Citations
“…The 1.7-and 2.3-μm windows have mainly been used for quantification of gas abundances such as CO, H 2 O and HCl (e.g., Bezard and de Bergh 2007;Tsang et al 2008;Iwagami et al 2008Iwagami et al , 2010Marcq et al 2008;Barstow et al 2012;Arney et al 2014) below the cloud (not exactly at the surface). They found an average H 2 O abundance of 25-35 ppmv with nearly uniform hemispherical distribution.…”
Section: Introductionmentioning
confidence: 99%